Avaliação da atividade genotóxica, citotóxica e histopatológica de imunossupressores em diversos níveis celulares e organismos - Oliveira, Laís Camargo de (2019)
Prednisone (PD) and azathioprine (AZA) are widely used in the immunossupressive therapy of transplanted and autoimmune disease patients. The chronic use of immunossupressants has been correlated with the occurrence of several side effects and also with the increase of neoplasia in those patients. Considering that genotoxic activity is associated to the increase of risk of cancer development, this study evaluated mutagenic, genotoxic and cytotoxic activities PD and AZA using in vitro and in vivo assays. The mutagenic activity was evaluated using mutagenicity Ames test in Salmonella typhimurium TA100 strain. The evaluation of genotoxicity and cytotoxicity was performed using micronucleus and comet assays in mouse bone marrow cells. Moreover, it was evaluated the toxic effects of PD and AZA in organs (liver and kidneys) of mice. In the mutagenic Ames test PD didn’t showed significant difference compared to the negative control in all tested doses (p > 0,05). In contrast, AZA exhibited significant increase compared to negative control in the two higher doses (20 and 40 μg/plate) (p < 0,05). In the micronucleus test, PD showed genotoxic activity in all tested doses and times and was cytotoxic in two of the tested doses (1,0 mg/kg in 48 hours and 0,5 mg/kg in 120 hours). In the comet assay, PD showed high porcentage of DNA damage in all tested doses and times. Furthermore, the 120 hours treatment presented the highest genotoxic activity when compared to the other PD tested groups (p < 0,05). In the same assay, AZA showed significant increase in all doses and times of treatment when compared with negative control (p < 0,05). In the histopathological analyzes, it was observed a moderate to accentuated congestion in mice liver treated with PD and a discrete hyperemia in mice liver when treated with AZA. Therefore, PD did not showed mutagenic activity in Ames test, however it was genotoxic and cytotoxic in the in vivo assays, and presented moderated toxic effect in the histopatological analyses. AZA exhibited mutagenic and genotoxic activity in several genotoxicological assays performed, however it did not cause relevant toxicity in mice tissues.